Causal relationship between gut microbiota and pathological scars: a two-sample Mendelian randomization study - Shucheng, Huidi; Li, Jiaqi; Liu, Yu-ling; Chen, Xinghan; Jiang, Xian (Frontiers in Medicine, 2024)
Background Pathological scars, including keloids and hypertrophic scars, represent a significant dermatological challenge, and emerging evidence suggests a potential role for the gut microbiota in this process. Methods Utilizing a two-sample Mendelian randomization (MR) methodology, this study meticulously analyzed data from genome-wide association studies (GWASs) relevant to the gut microbiota, keloids, and hypertrophic scars. The integrity and reliability of the results were rigorously evaluated through sensitivity, heterogeneity, pleiotropy, and directionality analyses. Results By employing inverse variance weighted (IVW) method, our findings revealed a causal influence of five bacterial taxa on keloid formation: class Melainabacteria, class Negativicutes, order Selenomonadales, family XIII, and genus Coprococcus2. Seven gut microbiota have been identified as having causal relationships with hypertrophic scars: class Alphaproteobacteria, family Clostridiaceae1, family Desulfovibrionaceae, genus Eubacterium coprostanoligenes group, genus Eubacterium fissicatena group, genus Erysipelotrichaceae UCG003 and genus Subdoligranulum. Additional sensitivity analyses further validated the robustness of the associations above. Conclusion Overall, our MR analysis supports the hypothesis that gut microbiota is causally linked to pathological scar formation, providing pivotal insights for future mechanistic and clinical research in this domain.